The Reaction of 6-(4-Chloro-5H-1,2,3-dithiazol-5-ylidene)-4-methylcyclohexa-2,4-dien-1-one with Benzene-1,2-diamine: Synthesis and Chemistry of N-(2-Aminophenyl)-2-hydroxy-5-methylbenzimidoyl Cyanide - Koyioni, Maria; Koutentis, Panayiotis A. (Synlett, 2020)
(Z)-6-(4-Chloro-5H-1,2,3-dithiazol-5-ylidene)-4-methylcyclohexa-2,4-dien-1-one, readily prepared from 4,5-dichloro-1,3,4-dithiazolium chloride and p-cresol, reacts with benzene-1,2-diamine to give N-(2-aminophenyl)-2-hydroxy-5-methylbenzimidoyl cyanide. The latter, in acidic media, cyclizes to give, depending on the reaction conditions, 2-methylbenzofuro[2,3-b]quinoxaline, 2-(1H-benzo[d]imidazol-2-yl)-4-methylphenol or 2-(3-aminoquinoxalin-2-yl)-4-methylphenol.
Keywords: 1,2,3-dithiazole; imidazole; quinoxaline; benzofuran; ionizing power; carboxylic acid; heterocycle; cyclization